(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
Endolubricants are essential components in endodontic procedures, aiding in instrumentation, irrigation, and obturation of the root canal system. This article provides an in-depth exploration of the role, properties, types, applications, and considerations for the use of endolubricants in endodontics. Endolubricants reduce friction between instruments and canal walls, enhance the flow of irrigants, and promote the placement of obturation materials, ultimately contributing to the success of root canal treatments. Ideal endolubricants exhibit biocompatibility, appropriate viscosity, tissue solubility, and may possess antimicrobial properties. They can be classified into water-based, oil-based, gel-based, and chlorhexidine- based lubricants, each offering unique benefits. Endolubricants are applied during initial canal exploration, instrumentation, irrigation, and obturation stages. Considerations for endolubricant selection include compatibility with irrigants, biocompatibility, radiopacity, and ease of removal. Future advancements in nanotechnology hold promise for developing novel endolubricants with enhanced properties, contributing to improved endodontic outcomes.